Effect of pre-administered flurbiprofen axetil on the EC50 of propofol during anesthesia in unstimulated patients: a randomized clinical trial - Ma,Jing (2020)
Abstract Background and objectives Preoperative use of flurbiprofen axetil (FA) is extensively adopted to modulate the effects of analgesia. However, the relationship between FA and sedation agents remains unclear. In this study, we aimed to investigate the effects of different doses of FA on the median Effective Concentration (EC50) of propofol. Methods Ninety-six patients (ASA I or II, aged 18–65 years) were randomly assigned into one of four groups in a 1:1:1:1 ratio. Group A (control group) received 10 mL of Intralipid, and groups B, C and D received 0.5 mg.kg−1, 0.75 mg.kg−1 and 1 mg.kg−1 of FA, respectively, 10 minutes before induction. The depth of anesthesia was measured by the Bispectral Index (BIS). The “up-and-down” method was used to calculate the EC50 of propofol. During the equilibration period, if BIS ≤ 50 (or BIS > 50), the next patient would receive a 0.5 µg.mL−1-lower (or -higher) propofol Target-Controlled Infusion (TCI) concentration. The hemodynamic data were recorded at baseline, 10 minutes after FA administration, after induction, after intubation and 15 minutes after intubation. Results The EC50 of propofol was lower in Group C (2.32 µg.mL−1, 95% Confidence Interval [95% CI] 1.85–2.75) and D (2.39 µg.mL−1, 95% CI 1.91–2.67) than in Group A (2.96 µg.mL−1, 95% CI 2.55–3.33) (p = 0.023, p = 0.048, respectively). There were no significant differences in the EC50 between Group B (2.53 µg.mL−1, 95% CI 2.33–2.71) and Group A (p > 0.05). There were no significant differences in Heart Rate (HR) among groups A, B and C. The HR was significantly lower in Group D than in Group A after intubation (66 ± 6 vs. 80 ± 10 bpm, p < 0.01) and 15 minutes after intubation (61 ± 4 vs. 70 ± 8 bpm, p < 0.01). There were no significant differences among the four groups in Mean Arterial Pressure (MAP) at any time point. The MAP of the four groups was significantly lower after induction, after intubation, and 15 minutes after intubation than at baseline (p < 0.05). Conclusion High-dose FA (0.75 mg.kg−1 or 1 mg.kg−1) reduces the EC50 of propofol, and 1 mg.kg−1 FA reduces the HR for adequate anesthesia in unstimulated patients. Although this result should be investigated in cases of surgical stimulation, we suggest that FA pre-administration may reduce the propofol requirement when the depth of anesthesia is measured by BIS.